Optimasi Penugasan Pegawai Menggunakan Metode Hungarian - Riska Novtari Zendrato; Anita Sindar (Journal of Innovation Information Technology and Application (JINITA), 2019)
Various ways that companies use to minimize expenses, including maximizing available resources. The division of work is seriously handled aiming that each employee gets a maximum wage according to the work hours specified by the company. Completion of the Hungarian method that is the number of employees employed must be equal to the amount of work that must be completed then in the study the data source of seven employees and seven jobs resulted in a minimum total funding. Optimization is the process of optimizing available resources in order to get effective and efficient results. The Hungarian method uses rows and columns to be an effectiveness matrix until a single zero component appears in each row or column that can be selected as assignment allocation. The division of tasks is the maximum if the employee does one job in one time period. To minimize the budget expenditure for overtime salary payments, minimization of funding sources and time spent on completing work are carried out. The results of research using the Hungarian Method, obtain financing minimization with one employee doing one job. Order of optimization results of minimization of assignments III, VII, VI, II, I, V and IV.